Contribution of Corporate Social Responsibility (CSR) of multinational companies in Indonesia during the COVID-19 pandemic - adelia, Adelia Prida Safasyahdani (Universitas Ahmad Dahlan, 2022)
The purpose of this study is to explain the various CSR contributions of multinational companies in Indonesia during the Covid-19 pandemic, especially for the community and affected parties. The research method used is descriptive qualitative with in-depth analysis to describe the topic of the problem to be studied. The final results of this study indicate that in improving the quality of life and empowering the community and surrounding agencies and communities during the Covid-19 pandemic, various multinational companies in Indonesia also contribute to social responsibility. The implementation of CSR of multinational companies in Indonesia to the public during the Covid-19 virus outbreak has the opportunity to make changes for the better in channeling social responsibility contributions with development goals in the long term to achieve balance with the community and stakeholders. Several multinational companies in Indonesia that are used as samples in this study are CSR contributions carried out by PT Unilever Indonesia, PT Gojek Indonesia, PT Asuransi Allianz Utama Indonesia, Danone Indonesia, PT Nestlé Indonesia during the Covid-19 pandemic. Most of the company's CSR programs are donations, based on this it can be seen that CSR contributions during the pandemic are aimed at affected communities, medical personnel, and communities or agencies.